ANALISIS SEKTOR EKONOMI UNGGULAN KAWASAN STRATEGIS MEBIDANGRO - Muslinawati, Retno; Azhari, Azhari; Aprilia, Nanda Dwi; Fadilah, Rika Nur (Universitas Riau Kepulauan, 2025)
This study was conducted to measure the level of economic development in various regions, classify economic sectors, and identify leading sectors in the National Strategic Area covering Medan City, Binjai City, Deli Serdang Regency, and Karo Regency (KSN Mebidangro). This study used quantitative descriptive analysis techniques utilizing GRDP data from 2019 to 2023. The analysis was conducted using several approaches, namely Klassen Typology, LQ, and DLQ. The results of the Klassen Typology analysis show that the City of Medan is classified as an advanced and rapidly developing region, while the City of Binjai, Deli Serdang Regency, and Karo Regency are categorized as advanced regions but still face pressures. Meanwhile, the results of the Location Quotient and Dynamic Location Quotient indicate that each city/district in the Mebidangro KSN has varying base sectors, consistent with the economic characteristics of each region. These findings emphasize the urgency of developing focused and effective policies to drive sustainable economic growth.